School health and nutrition services for children and adolescents in Tanzania: A review of policies and programmes - David Sando; Shinde Sachin; Grace Moshi; Mary‐Mwanyika Sando; Mashavu Yussuf; Anyitike Mwakitalima; Wafaie Fawzi (Maternal and Child Nutrition, 2025)
Abstract School health and nutrition programmes are effective strategies to address the health problems among school‐going children and adolescents. We examined the policy environments, successes and bottlenecks associated with school health and nutrition programmes in Tanzania. We used the ‘policy triangle framework’ to examine 22 national and regional school health and nutrition policies and programmes in Tanzania. We also interviewed 16 key informants to gain further insights into school health and nutrition programmes. Several school health and nutrition policies in Tanzania outline the basic elements of school‐based health and nutrition services. Yet, these documents neither recognise vulnerable groups, recommend age‐appropriate strategies to address children's and adolescents' varied and transient needs, nor provide a framework for implementing and tracking recommended activities. In these documents, underweight and infectious diseases, including human immunodeficiency virus/acquired immunodeficiency syndrome, are frequently identified as major concerns of young people, with little or no consideration of social determinants. Diverse strategies including school feeding, water and sanitation services, health and nutrition education and promotion of healthy behaviours are identified. In doing so, these documents adequately define the roles and responsibilities of all government actors, but young people and their guardians are not actively engaged in design and implementation. Additionally, there are several challenges to implementing these policies including budgetary constraints, limited resources, a lack of inter‐sectoral coordination and insufficient capacity within targeted schools. To improve the health and nutritional status of school‐going children and adolescents in Tanzania, adequate budgets, strengthened coordination and implementation efforts, the development of school‐based stakeholders' capacity, as well as the involvement of all other stakeholders, including adolescents, are imperative.